Selected aspects of the use of artificial neural networks for the mass appraisal of real estates in Poland - Wiśniewski, Radosław (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
Mass appraisal is a specific process of property valuation employing mass appraisal methods. The results of recent research and practical implementation show that property value estimation may be based oil statistical methods. The aims of the present study Were is follows: (1) to discuss the possibilities of an artificial neural network application (ANN MLP - Multi-Layer Perceptron), (2) to describe the specific characteristics of ANN; (3) to evaluate the obtained results and (4) to develop the methodology of ANN application ill the mass appraisal of real estate m Poland. The results obtained using multiple repression models were compared with those obtained using ANN MLP models
Argumenta Oeconomica, 2008, No 2 (21), s. 125-152
Keywords: mass appraisal; artificial neural networks; regression; valuation of real estates; sztuczne sieci neuronowe; wycena nieruchomości; modele regresji